2023
DOI: 10.9734/ijpss/2023/v35i92904
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphorous and Vermicompost on Growth Characterstics and Yield of Chickpea (Cicer aretinum L.)

Abstract: A field experiment was conducted at Rajaula Agriculture farm, of Mahatma Gandhi Chitrakoot Gramodaya Vishwavidyalaya Chitrakoot, Satna (M.P.) during Rabi season of 2021-22. To study the effect of phosphorous and vermicompost on growth parameters, yield components and yield of chickpea the experiment comprised of 12 treatment combinations in randomized block design with three replications. Chickpea variety GNG-1958 (Marudhar) was grown with the recommended agronomic practices. On the basis of the results emanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…T6). These results reflect a more significant effect of PRM years after its application as already indicated in various studies [16.28.29.27] which have indicated that the application of phosphate rocks generates residual effects in the years following their application [30][31][32].…”
Section: Backward Effect Of Phosphate Amendments On Rice Yieldsupporting
confidence: 76%
“…T6). These results reflect a more significant effect of PRM years after its application as already indicated in various studies [16.28.29.27] which have indicated that the application of phosphate rocks generates residual effects in the years following their application [30][31][32].…”
Section: Backward Effect Of Phosphate Amendments On Rice Yieldsupporting
confidence: 76%